1989
DOI: 10.1007/bf00033468
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient utilization during biomass and anthocyanin accumulation in suspension cultures of wild carrot cells

Abstract: The medium used for the growth of anthocyanin-accumulating wild carrot (D. carota) suspension cultures contained ammonia as a sole nitrogen source and was buffered with succinate. Ammonia was the first nutrient to be completely utilized.The uptake of carbohydrate, phosphate and succinate continued after ammonia depletion. Biomass accumulation was faster and greater when sucrose was initially present in the medium than when glucose was present. When sucrose was provided in the medium it was rapidly hydrolysed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…-0.1 MPa was observed at day 3 of culture and could be attributed to the increase in the concentration of reducing sugars [3]. It is generally recognized that plant cell cultures hydrolyse sucrose extracellularly into reducing sugars prior to their assimilation [1,4]. Thus, the decrease in the osmotic potential which followed day 3 of culture could be attributed to the assimilation of sugars.…”
Section: Resultsmentioning
confidence: 92%
“…-0.1 MPa was observed at day 3 of culture and could be attributed to the increase in the concentration of reducing sugars [3]. It is generally recognized that plant cell cultures hydrolyse sucrose extracellularly into reducing sugars prior to their assimilation [1,4]. Thus, the decrease in the osmotic potential which followed day 3 of culture could be attributed to the assimilation of sugars.…”
Section: Resultsmentioning
confidence: 92%
“…1). This effect is well known and seems to be due to acid invertases which are localized in the medium and in the cell walls [1,6,13]. Thereafter the hexoses were actively consumed in all media, except in medium containing 24mM ammonium ions where sugars were assimilated more slowly.…”
Section: Nutrient Consumption In the Culture Mediamentioning
confidence: 92%
“…In Euphorbia millii cells, anthocyanin production was inhibited by high concentrations of ammonium ion [26]. In wild carrot cell cultures, the correlation between anthocyanin accumulation and ammonia levels in the medium suggested that ammonia in excess of 3-5 mM in the medium inhibited anthocyanin accumulation [6]. and low nitrate ions repressed the formation of anthocyanin [25].…”
Section: Anthocyanin Formationmentioning
confidence: 95%
“…Most published data on nutrient utilization in vitro were generated from cell suspension cultures (Dougall 1980;Dougall & Frazier 1989;MacCarthy et al 1980;McDonald & Jackman 1989;Martin & Rose 1976). Information on nutrient uptake in organ (shoot) cultures is limited.…”
Section: Introductionmentioning
confidence: 97%